Stanley Jaki’s Criticism of Platonic Philosophy - Giostra, Alessandro (Alpha omega, 2018)
In all of his works Stanley L. Jaki (1924-2009) has emphasized the key role playedby Christian doctrine in relation to the emergence of exact sciences. Adhesion to the basic principles of Christian revelation implies opposition to pantheistic worldviews, Platonism being one of their major philosophical expressions. This paper analyses in more detail the position held by the Hungarian philosopher on the cosmological views of Plato, Plotinus, and Giordano Bruno. Although they belonged to different epochs, we can find in their animistic conceptions a common ground to reject this modern approach to the investigation of nature.